Comparative analysis of the effectiveness of surgical treatment of macular hole with and without postoperative gas tamponade of the vitreal cavity - A.Yu. Kleymenov; V.N. Kazaykin; M.A. Lipina (Офтальмохирургия)
Purpose. To compare the anatomical and functional results of surgical treatment for full-thickness macular holes with and without the gas tamponade of the vitreous cavity. Material and methods. The study included 2 groups of patients. All surgeries were performed at the Ekaterinburg Branch of the Fyodorov Eye Microsurgery Federal State Institution in the period from 2018 to 2020. In the 1st group (30 eyes), the traditional MH treatment technology was used, patients in the second group (30 eyes) were treated without the use of tamponade, according to the method developed at the center. In the 1st group, the minimal diameter of the macular hole was from 194 to 755 (446.43±32.37) μm, the best corrected visual acuity (BCVA) – from 0.04 to 0.4 (0.16±0.02). The minimal diameter of the macular rupture in the 2nd group was from 100 to 932 μm (558.5±50.9), BCVA – from 0.02 to 0.25 (0.11±0.02) (p>0.05). The follow-up period was 1 to 20 months (8.9±0.8). Results. Complete closure of the macular hole in the early postoperative period: 1st group was achieved in 29 out of 30 cases (96.6%), 2nd group – in 30 out of 30 cases (100%). BCVA on the first day after the surgery: 1st group – from 0.005 to 0.15 (0.02±0.01), 2nd group – from 0.08 to 0.35 (0.2±0.02) (p<0.001) BCVA 1 year after the surgery was in the 1st group – from 0.15 to 0.6 (0.43±0.07), in the 2nd group – from 0.3 to 0.7 (0.5±0.05) (p>0.05). Conclusion. Comparative analysis of the effectiveness of surgical treatment of through MH without the use of postoperative vitreal tamponade and the traditional method based on gas tamponade showed a significant reduction in the rehabilitation period for the method without tamponade.